The Analysis of QirÄ'ah MubÄdalah on the Meaning of Women's Deception in QS. Yusuf [12]: 28) - Rosy, Fathor (AL QUDS : Jurnal Studi Alquran dan Hadis, 2024)
The aim of this article is to analyze the meaning of women's deceit contained in QS. Yusuf [12]: 28. The meaning of women's deceit that is so powerful is accepted and interpreted textually which is then adopted by the community without paying attention to the context of the verse. This article will look at the contextual aspect of the verse through QirÄ'ah MubÄdalah. QirÄ'ah MubÄdalah is an analytical tool initiated by Faqihuddin Abdul Qodir. First, it determines and affirms the principles in Islamic teachings contained in universal texts that are the basis of understanding. Secondly, finding the core thoughts stored in the texts to be interpreted. Third, deriving the main idea from the text contained in the second step to the gender that is not mentioned in the text. This research is a qualitative research that uses primary sources and secondary sources. Primary sources in this research are books of interpretation that explain QS. Yusuf [12]: 28. Secondary sources are articles, and encyclopedias that support this research. This article will ask questions. How is the contextual interpretation of QS. Yusuf [12]: 28 by using QirÄ'ah MubÄdalah. Through QirÄ'ah MubÄdalah, this research results in that the universal meaning of deceiving women is the attitude of throwing responsibility or actions that have been carried out and telling lies which are prohibited acts in Islamic teachings.